Enzymatic Degradation of Multiple Major Mycotoxins by Dye-Decolorizing Peroxidase from Bacillus subtilis - Xing Qin (Toxins, 2021)
The co-occurrence of multiple mycotoxins, including aflatoxin B1 (AFB1), zearalenone (ZEN) and deoxynivalenol (DON), widely exists in cereal-based animal feed and food. At present, most reported mycotoxins degrading enzymes target only a certain type of mycotoxins. Therefore, it is of great significance for mining enzymes involved in the simultaneous degradation of different types of mycotoxins. In this study, a dye-decolorizing peroxidase-encoding gene BsDyP from Bacillus subtilis SCK6 was cloned and expressed in Escherichia coli BL21/pG-Tf2. The purified recombinant BsDyP was capable of oxidizing various substrates, including lignin phenolic model compounds 2,6-dimethylphenol and guaiacol, the substrate 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid), anthraquinone dye reactive blue 19 and azo dye reactive black 5, as well as Mn2+. In addition, BsDyP could efficiently degrade different types of mycotoxins, including AFB1, ZEN and DON, in presence of Mn2+. More important, the toxicities of their corresponding enzymatic degradation products AFB1-diol, 15-OH-ZEN and C15H18O8 were significantly lower than AFB1, ZEN and DON. In summary, these results proved that BsDyP was a promising candidate for the simultaneous degradation of multiple mycotoxins in animal feed and food.